3-phase 4-wire hybrid calculation - Analysis method for clustering power systems philosophy - Paramet Wirasanti (2018)
© 2015 IEEE. Clustering power systems approach has been recently introduced as a strategy for power systems automation - smart grid. The key concept of clustering power systems approach is to extend the system structure and the control approach of transmission level down to distribution level. Hence, a cluster network structure and a downsizing of conventional control function to distribution level are researched. Consequently, this paper is targeted on cluster power flow analysis, which is a part of downsizing tertiary control function. However, there is a complexity of cluster analysis due to the flexibility adaptation of cluster network. To overcome this issue, a decoupling analysis approach for each cluster area is required. Based on previous investigations, a hybrid calculation is pointed out as a key technique for the decoupling analysis. Nevertheless, to execute power flow analysis in distribution level, an asymmetrical condition, e.g. single phase loads and mixed feed-in, cannot be ignored. Furthermore, an analysis of neutral wire is important regarding protection standard on IEC 60364-1 in low voltage level. The neutral wire analysis is also one of the indicators to observe power balanced condition. Thus, a three-phase four-wire power flow analysis based on hybrid calculation is proposed in this paper. To guarantee, the proposed method is verified by comparing the results with the DIgSILENT PowerFactory program. In addition, the proposed method can be utilized not only for the clustering power systems analysis but also for the general purpose power flow analysis.